СТУДЕНТ ЖАСЛАРДА СИЯСИЙ ТӘРБИЯ КӨНЛИКПЕСИН РАЎАЖЛАНДЫРЫЎ – ПЕДАГОГИКАЛЫҚ ЗӘРҮРЛИК СЫПАТЫНДА - Ешимбетова, Гулзар Турымбетовна (ILIM hám JÁMIYET, 2026)
The article examines one of the most pressing issues of our time – increasing the political literacy of young people, the state of work in this area and the main directions of development of pedagogy.